2001
DOI: 10.1097/00129492-200111000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Implant: Part I. Auditory Performance and Its Evolution Over Time

Abstract: Although auditory sensation appeared immediately after device activation, a period of 6 months was necessary for relearning and adaptation of the central auditory system to the altered form of auditory information presented by the auditory brainstem implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 8 publications
4
46
0
6
Order By: Relevance
“…All children used their ABI regularly on a daily basis, and similar to the findings in the literature, they were found to develop awareness toward environmental sounds and speech sounds after 1-month to 3-month intervals [11][12][13][14] . Functionality of auditory perception skills was mostly evaluated with MAIS/IT-MAIS in researches; however, in our research, FAPCI was conducted to determine auditory functioning and compared with normally hearing population.…”
Section: Discussionsupporting
confidence: 80%
“…All children used their ABI regularly on a daily basis, and similar to the findings in the literature, they were found to develop awareness toward environmental sounds and speech sounds after 1-month to 3-month intervals [11][12][13][14] . Functionality of auditory perception skills was mostly evaluated with MAIS/IT-MAIS in researches; however, in our research, FAPCI was conducted to determine auditory functioning and compared with normally hearing population.…”
Section: Discussionsupporting
confidence: 80%
“…Speech results in the AMI patients, particularly for AMI-3 who is implanted in the intended target (ICC), are comparable with what are observed in ABI NF2 patients at 6 months. Of 11 ABI NF2 patients tested in our clinic using the same protocols (the same speech therapist tested all the ABI and AMI patients) (Lenarz et al, 2001), only four exceeded the 11 words per minute enhancement achieved by AMI-3. Five ABI patients performed worse than AMI-1 and AMI-2 (less than two to three words per minute).…”
Section: Speech Perception and Environmental Awarenessmentioning
confidence: 86%
“…The German speech tests below are similar to those used in our clinic for assessing CI and ABI patients (Strauss-Schier et al, 1995;Rost and Strauss-Schier, 1998;Lenarz et al, 2001). They were performed in live voice under lip reading alone, lip reading plus the AMI, and AMI alone.…”
Section: Speech Testsmentioning
confidence: 99%
“…The aetiology of vestibular schwannomas is widely unknown, whereas in neurofibromatosis a polyclonal origin is suspected 8 . Neurofibromatosis type is a hereditary disease associated with VS.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity and quality of hearing rehabilitation is increasing from normal hearing aids, cross-and bicross-hearing-systems, bone conducted hearing aids, middle ear implants (MOI), cochlear implantation (CI), auditory brainstem implant (ABI) and auditory midbrain implant (AMI). After surgical removal of VSs, especially in neurofibromatosis type 2 patients, the supply with ABI is in most cases an option, but several studies showed an unsatisfactory outcome 8,11,13,14 . Especially the speech perception with an ABI in adults 15 , compared to the supply in young children 16 , is a huge breakdown.…”
Section: Introductionmentioning
confidence: 99%